한국 코로나바이러스감염증-19 환자 5,628명의 역학적, 임상적 특성: 전국단위 다기관 관찰 연구 - 이승원; 문성용; 연동건 (Allergy asthma & respiratory disease, 2021)
Purpose: There are limited data on the epidemiological and clinical characteristics and outcomes in Korean patients with laboratory-confirmed coronavirus disease 2019 (COVID-19). We aimed to describe the epidemiological and clinical characteristics and outcomes of patients with COVID-19 using the Korean nationwide multicenter database. Methods: In this nationwide multicenter study, we included all confirmed patients of COVID-19 in South Korea from February 1 to April 30, 2020. Subjects were classified into 3 age groups: those at younger than 10 years (children), 10 to 20 years (adolescents), and 20 years or more (adults). Cases were confirmed by laboratory testing using real-time reverse transcriptase-polymerase chain reaction assay and analyzed for epidemiological and clinical features and outcomes. Patents were followed up until April 30, 2020. Results: Of 5,628 patients with COVID-19 (2,320 males [41.2%] and 3,308 females [58.8%]), there were 66 children (1.2%), 206 adolescents (3.7%), and 5,356 adults (95.2%). The common comorbidities were hypertension (1,201, 21.3%), diabetes (691, 12.3%), dementia (224, 4.0%), chronic heart disease (179, 3.2%), cancer (145, 2.6%), and asthma (128, 2.3%). The common presenting symptoms were cough (2,341, 41.6%), sputum (1,619, 28.8%), fever (1,305, 23.2%), headache (967, 17.2%), myalgia (926, 16.5%), and pharyngodynia (881, 15.7%). One hundred sixty-five patients (2.1%) were confirmed as having moderate or severe COVID-19 and 118 (2.1%) as having severe COVID-19. Conclusion: Our descriptive study provides the epidemiological and clinical characteristics and outcomes of patients with laboratory-confirmed COVID-19 in South Korea. KCI Citation Count: 2